Ion cyclotron waves: a tool for characterizing neutral particle profiles in extended exospheres - Lammer, Helmut; Schmid, Daniel; Volwerk, Martin; Weichbold, Fabian; Wedlund , Cyril Simon; Varsani, Ali; Delva, Magda (Frontiers in Astronomy and Space Sciences, 2025)
Planetary exospheres are usually observed using transit spectroscopic methods, such as the Lyman-α line, which is mainly limited by interstellar medium absorption and airglow contamination from the geocorona when using low-orbit space telescopes or neutral and ion particle detectors and flight mass spectrometers. In this study, we discuss a complementary method that can be used for the characterization of exospheres based on the analysis of so-called ion cyclotron waves (ICWs) using magnetometers and plasma instruments. These ICWs are produced by pick-up ions from exospheric neutral atoms over a large spatial region upstream of planetary bodies. The newborn exospheric ions generate an unstable secondary ion population in the solar wind plasma, where the interaction between the exospheric and solar wind ion populations can produce plasma waves arising from various instabilities. The observed wave power can be used to derive the corresponding pick-up ion and related neutral particle densities. Because the ion pick-up density is balanced by the ion production rate, one can reconstruct the exospheric neutral number density. Various exospheric particles (i.e., H, H2, D, He, etc.) can be distinguished by identifying their masses via their different gyrofrequencies even when they are very close to each other. In this study, we will discuss and analyze available ICW data as a tool for the reproduction of neutral atom profiles of extended exospheres, such as those of Mercury, Venus, Mars, the Jovian satellites, and comets.